Neutrophils dominate in opsonic phagocytosis of P. falciparum blood-stage merozoites and protect against febrile malaria - Asier Garcia-Senosiain (Nature Portfolio, 2021)
Garcia-Senosiain et al developed an in vitro opsonic phagocytosis (OP) assay using peripheral blood leukocytes that enabled quantification of the contribution of each phagocytic cell type in the OP of Plasmodium falciparum blood-stage merozoites, which have been associated with malaria protection. Using patient samples from Ghana and India, they demonstrate that peripheral blood neutrophils are the main phagocytes of P. falciparum blood-stage merozoites